Hydropower Atlas of Madagascar - World Bank (Washington, DC, 2017)
Madagascar has enormous energy resources, particularly renewable ones (hydraulic, solar, wind, biomass), but national energy consumption is still very low, and is dominated by wood energy and its by-products. Madagascar imports all of its petrol products, and energy costs are too high to effectively contribute to social and economic development of the country. ESMAP (Energy Sector Management Assistance Program) is a technical assistance program managed by the World Bank and supported by eleven bilateral donors. ESMAP launched in January 2013 as an initiative to support the efforts of countries to improve knowledge of their renewable energy resources (REN), to establish appropriate institutional frameworks for the development of REN, and to provide free access to geospatial resources and data. This initiative will also support the IRENA-GlobalAtlas program by improving data availability and quality, through an interactive atlas. This study is part of a technical assistance project funded by ESMAP and implemented by the World Bank in Madagascar , which aims to support mapping resources and geospatial planning for small hydropower. It is conducted in close coordination with the Ministry of Energy, the Electricity Regulation Office (ERO), Development Agency of Rural Electrification (DARE) and Jiro sy Rano Malagasy (JIRAMA).